From Silence to Social Awakening: Exploring the Personal Trajectories of Activists in Morocco’s Post-Arab Spring Movements - Youssef, Imane Ben; Khalil, Jamal (European Scientific Journal, ESJ, 2024)
The Arab Spring served as a catalyst for various movements aiming to implement political change across the Arab world. Morocco, with its rich history of social movements, witnessed the emergence of the Movement of 20th February 2011 (M20F), the Hirak Rif, and the 2018 boycott campaign. The M20F, in particular, challenged the established fear imposed by the Makhzen, marking a transformative moment facilitated by social media and a call against "hogra" – oppression, injustice, and social contempt. While existing studies have focused on the political and social factors behind activism and the consequences of these movements on societies, the present paper takes a more individualistic perspective. Using biographic interviews with several activists from these uprisings in Morocco, and from different backgrounds and affiliations, the paper examines their life trajectories with the aim of understanding what factors influenced their decision to join a movement and the subsequent impact on their lives. This paper presents the profiles of six activists and discusses the rationale behind shaping their activist careers. The respondents developed an interest in activism from various influences—parental, cultural, media, socio-economic conditions, and experiences of marginalization—all united for a common objective of change, despite diverse ideologies.